Climate Report from the United States. (3rd April 2018) - Bay-Cheng, Sarah
Abstract : This performative provocation replays a moment of political anticipation leading up to the US presidential election of 2016 and reflects on those sentiments with musical accompaniment by the Rolling Stones.